DIVERSIDAD VEGETAL EN UN REMANENTE DEL CHOCÓ, ESMERALDAS - ECUADOR - Cerón, Carlos (2007)
The place of study fits to the ecological corridor Awa - Cachi administered by the Foundation SIRUA, they are a part of ¡mportant hydrographic basins as those of the rivers: Tulubí, Bogotá, Carolina and Negro, belong to the parishes Durango and High place Tambo, province of Emeraldas, altitude between 179 and 640 m, zone of lite very humid tropical forest. From july until october, 2005, 7 localities were sampled using the methodology of transects, radial model and for species equal or major than 2.5 cm of DAP. Of every individual samples were realized for herbalist, the same ones that mounted and identified settled in the herbarium Alfredo Paredes (QAP). There were calculated the índexes of Simpson's Diversity and that of Sorensen's similarity. The number of individuáis changes between 149 - 223, and the number of species between 56 - 75, all the samplings add a whole of 256 species. Of these 18 they are endemic. The valúes of the Índex of diversity changes from down to near the average, the similarity ranges between 7.6 % and 38.5 %. Common species to the majority of the samplings are 38 Cerón et al.: Diversidad vegetal, Chocó Wettinia quinaria and Pholidostachys dactyloides (Arecaceae) and in the places ¡surrounds to the rivulets and rivers Palicourea acanthacea (Rubiaceae). The State of the remnants in general, they are disturbed due to the continuous extraction of wood as the chanul, sande, copal, anime, etc. Before the threat of disappearance of the latter remnants of Choco ecuadorian, there is important the research of the same one, conservation and delineations of alternatives of sustainable managing, leaving the aggressive felling of the wood and furthermore the replacement with plantations of monocultures as the African palm. INTRODUC